Self-evaluation of ISO 9001:2015 Standard elements within a group of Costa Rican MSMEs (National Administration Journal, 2019)
Micro, small and medium-sized Costa Rican companies play a significant role in the economic growth of the country. Providing quality products and services in a sustained manner is unavoidable, however, the practice of an organizedsystem that helps them to control its quality is usually a difficult task. Universidad Fidélitas and the Chamber of Exporters of Costa Rica, conducted a self-rating survey from July to October 2018 to a group of companies of this type to know how they manage their quality (with reference to ISO 9001: 2015) considering variables as: size of the company, sector and condition of export. The results show that the main variable is the size of the company, since as the number of employees increases, the principles of the Standard are more robustly applied. Sections of the Standard that imply execution and monitoring activities were evaluated at a lower level.
Keywords: Service; Quality; Education; University, Satisfaction